Nanomechanical and optical vibrations properties of vanadium oxide thin films obtained by multi-step deposition approach - Korchoviy, Andrii; Lytvyn , Petro; Dzhagan , Volodymyr; Gudymenko, Olexandr; Svezhentsova, Kateryna; Boltovets, Mykola; Strelchuk, Viktor; Kolesnikov, Olexandr; Isaieva, Oksana; Yefanov, Volodymyr; et al. (Physics and Chemistry of Solid State, 2024)
Vanadium oxide thin films were fabricated using a multi-step deposition process involving magnetron sputtering and sequential annealing. The structural, vibrational, and nanomechanical properties of the films were investigated to elucidate the impact of phase composition on the performance of metal-insulator phase transition (MIT). X-ray diffraction (XRD) and Raman spectroscopy revealed a structural evolution from quasi-amorphous to nanocrystalline phases upon annealing, with transitions from VO₂ to textured V₄O₉ dominating the annealing process. The observed phase transition is accompanied by hardness increase from 0.9 GPa in the amorphous first layer to 11–18 GPa in all (crystalline) multi-layers. The hardening is attributed to development of well-ordered crystalline texture, which improved interatomic bonding and resistance to deformation. The vibrational Raman spectra obtained at various excitation wavelengths exhibit resonant sensitivity to different oxide phases, including the minority V3O7 phase not detectable by XRD and selective resonant probe of V4O9 phase only with 671 nm excitation. Temperature-dependent Raman and electrical resistivity measurements revealed superior MIT characteristics for samples with higher VO₂ content, despite the presence of other VₓOᵧ phases. These findings underscore the critical role of structural ordering in tuning the mechanical and functional properties of vanadium oxide films for advanced electronic and optical applications.